A Model of Autonomous Control of the Adaptation to the Context in UbiComp - Warken, Nelsi; Yamin, Adenauer; Lopes, João L. B.; Dilli, Renato; Venecian, Luthiano; Rodrigues, Sergio (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
The research presented in this paper has as main purpose the conception of a mechanism to control the adaptations the context of component-based applications in Ubiquitous Computing, considering the context produced by monitored information, semantic information and inferences from these informations. The premise is to culminate in a model of adaptation, which can be used both by middleware services, as by applications. For this we propose the use of the concepts and technologies related to Semantic Processing and Autonomous Systems in designing a mechanism for control of dynamic adaptation. The conceived model has compared his contributions to the state of the art, and was evaluated by two case studies, with satisfactory results as to meet the demands of ubiquity.